Pengaruh Struktur Modal, Ukuran Perusahaan dan Solvabilitas Terhadap Economic Value Added - Salsa Bila Andini; Hari Setiono; M. Bahril Imiddaviq (Indonesia Economic Journal, 2026)
This study aims to examine how capital structure, firm size, and solvency affect Economic Value Added (EVA) in banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period. EVA is utilized as a financial performance indicator because it reflects a company's ability to generate economic value after deducting the cost of capital. The study employs a quantitative approach using a causal-associative method. A purposive sampling method was used to select the sample, resulting in 42 banking companies and a total of 168 observations. Data analysis techniques include descriptive statistics, classical assumption testing, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that, individually, capital structure significantly affects EVA, whereas firm size and solvency do not have a significant effect. However, the three variables collectively exert a significant influence on EVA. These findings demonstrate that effective capital structure management is crucial for creating economic value within banking companies.